The effectiveness of combination therapy package based on acceptance and commitment, mind-awareness, and schema therapy on interpersonal relationships among men and women with obsessive-compulsive disorder - Allahverdi, Nilofar; Zarbakhsh, Mohammadreza; Khalatbari, Javad; Rahmani, Mohammad Ali (Applied Family Therapy Journal (AFTJ), 2021)
Aim: This study aimed to determine the effectiveness of a combination therapy package based on acceptance and commitment, mind-awareness, and schema therapy on interpersonal relationships among men and women with obsessive-compulsive disorder. Methods: This research was conducted with the experimental method and a pretest-posttest design with a control group and a three-month follow-up stage. According to the inclusion criteria of the study, all male and female clients of Nikta Clinic with the diagnosis of obsessive-compulsive disorder completed the interpersonal communication skills questionnaire of Matson et al. (1995) in the pre-test stage. And the number of 77 people who obtained a low standard deviation lower than the considered score (below 62) were screened in this questionnaire, and 30 people were randomly selected and assigned to 2 experimental and control groups (15 people in each group). Afterward, the experimental group received twenty sessions of 120 minutes and two sessions of the combination therapy package per week. At the end of the treatment period, both groups were asked to complete the research questionnaire again in the post-test stage. The data were analyzed using repeated-measures analysis of variance. Results: The findings indicated that the combination therapy package had an impact on interpersonal relationships in the experimental group (F = 30.12, P < 0.001), and this effect was stable at the follow-up stage (p < 0.001). Conclusions: According to the results of this study, given that with awareness of acceptance and commitment to the received training and strengthening awareness along with using schema therapy training, people acted effectively in improving interpersonal relationships, the combination of these three approaches will be effective in advancing therapeutic goals in the treatment of people with obsessive-compulsive disorder.